EFEKTIVITAS PROGRAM PENATAAN LINGKUNGAN PERMUKIMAN BERBASIS KOMUNITAS DI KELURAHAN TITIWUNGEN UTARA KECAMATAN SARIO KOTA MANADO - PUTRI, DIAN ANGGREINI; Dengo, Salmin; Londa, Very (Sam Ratulangi University, 2017)
ABSTRACT: The program of Neighborhood community-based Environment (PLPBK) isbasically an advanced interventions within the framework of a strategy of intervention UrbanPNPM Mandiri. The activities of PLPBK give priority to the harmonisation of synergies betweenthe regional programme, the community and the groups concerned in the process of structuringthe environment independently and sustainable settlements.This research aims to know the effectiveness of PLPBK Program Settlements on thevillage's of northern Titiwungen, Sario Subdistrict in the City of Manado. This study usesqualitative methods. Informants in this study are 11 people. Data collection instruments andtechniques used are guidelines for interviews and assisted with interviews and observation.Measuring the effectiveness of this program using the theory of Barnard in Prawisentono with 9indicators measuring effectiveness i.e. the clarity of purpose, clarity of program strategy goalachievement, a program of steady policy formulation, drafting of appropriate programs, theprovision of facilities and infrastructure, operational effectiveness, functional programseffectiveness, the effectiveness of the objectives of the program and the effectiveness of theprogram target.The results of this study claimed that using the 9 indicators in measuring the effectivenessof an environmental Setup program Neighborhood-based Community votes is effective enough.Thus it can be concluded when the effectiveness of an environmental Setup program communitybasedSettlements in Kelurahan of northern Titiwungen of the City of Manado, has been runningquite effectively.Key Words: Effectiveness of programs